Educational investigation for the postgraduate training of teaching staff in medical education - Nadina Travieso Ramos (Centro Provincial de Información de Ciencias Médicas, 2018)
In this investigation the curricular microdesign of the didactic unit "Methodology of the educational investigation in health" was elaborated and the feasibility of its implementation was evaluated during the Certification in Medical Education that took place at the University of Medical Sciences in Santiago de Cuba during the school course 2016-2017, for which an exploratory study was carried out with all the teachers registered. The variable relevance and coherence were used as evaluative criteria, and the data were obtained by means of the documental analysis and survey. The results were analyzed through the relative frequency.  The feasibility of implementation of the didactic unit, demonstrated through its relevancy and coherence, makes of this an alternative proposal for the didactic improvement of health investigation methodology in the postgraduate training of these teachers.